Modelling effectivenes of IS learning methodology with AHP method - Yunaeti Anggraeni, Elisabet; ., Pardimin; Dacholfany, Ihsan; ., Akla; Huda, Miftachul; Shukri Mat Teh, Kamarul; Hehsan, Aminudin; Junaidi, Juhazren; Mohd Yusof, Farahwahida; Abas, Hafiza; Fauzi Abu Husin, Mohd; Apriani, Dina; et al. (International Journal of Engineering and Technology, 2018)
Information system research methodology, Bahasa: Metodologi Penelitian Sistem Informasi (MPSI), is a mandatory course that must be attended by information system and management student at STMIK Pringsewu. MPSI learning must be conducted effectively to achieve the expected goal. The problem is how to determine MPSI learning effectiveness at STMIK Pringsewu. This problem must be done by Analytical Hierarchy Process method. AHP method can help solving complex problem by structuring a hierarchy criteria, party who has interest, result and by attract some consideration to develop weight and priority. The results of this research was a decision support system which adapts related party in determining learning effectiveness of MPSI at STMIK Pringewu. From this research result obtained a conclusion that is MPSI learning at STMIK Pringsewu is very effective with score of 2.138.